(3OjhGf GHf GdaGQVs - (3GHf GdaGQV (B- (3SdWGf GdYGTbjf , YeQ Hf Ydj Hf eQTO Hf Ydj GdMehj, TQa GdOjf CHh MaU CHh GdbGSe,J (B632 (3g` s ((3CHhHcQ GdUOjb Hf GdebQj jhSa s)
(3ChdgG (B:s
(3eHJhQ, hChd GdehLhO efgG ef bUjOI PGdjI bhdg(B: (3hTcrJ HVGVg NOg ef hQOg hMcJ aXGXg bdHg GdahdGPG s
(3BNQgG (B:s
(3ef bUjOI dGejg bhdg(B: (3ade jHb efj eG jfGLj Jhgej Shi oYR Pdj aj egGHg ELdGdj s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdMGOj YTQs
(3fSNI NGeSIs
(3Ydi ghGeTgG HYV GdTQhM hGdJYdjbGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B216s
Keywords: (3GdCOHs